2019
DOI: 10.7874/jao.2018.00234
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of McGurk Effect across Three Consonant-Vowel Combinations in Kannada

Abstract: Background and ObjectivesThe influence of visual stimulus on the auditory component in the perception of auditory-visual (AV) consonant-vowel syllables has been demonstrated in different languages. Inherent properties of unimodal stimuli are known to modulate AV integration. The present study investigated how the amount of McGurk effect (an outcome of AV integration) varies across three different consonant combinations in Kannada language. The importance of unimodal syllable identification on the amount of McG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In the current study, ~15% of subjects (6/39) were classified as non-perceivers and excluded from further analysis as they did not perceive sensory fusion in at least 15% of McGurk trials [ 49 ]. The proportion of subjects not susceptible to the McGurk illusion is not universally reported in the literature, nor is there a standardized threshold subjects must meet to be considered a ‘perceiver / non-perceiver.’ This consideration notwithstanding, reported ranges for the proportion of non-perceiving subjects range from 0–54% [ 48 , 79 ] with an average of ~25% [ 54 ]. Among the subjects in the current study who reliably perceived the McGurk illusion, sensory fusion was reported in 73.5% of trials.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, ~15% of subjects (6/39) were classified as non-perceivers and excluded from further analysis as they did not perceive sensory fusion in at least 15% of McGurk trials [ 49 ]. The proportion of subjects not susceptible to the McGurk illusion is not universally reported in the literature, nor is there a standardized threshold subjects must meet to be considered a ‘perceiver / non-perceiver.’ This consideration notwithstanding, reported ranges for the proportion of non-perceiving subjects range from 0–54% [ 48 , 79 ] with an average of ~25% [ 54 ]. Among the subjects in the current study who reliably perceived the McGurk illusion, sensory fusion was reported in 73.5% of trials.…”
Section: Discussionmentioning
confidence: 99%